2019
DOI: 10.1097/md.0000000000017688
|View full text |Cite
|
Sign up to set email alerts
|

Adenosquamous carcinoma development as a recurrence of squamous cell carcinoma in the oral floor

Abstract: Rationale:Oral adenosquamous carcinoma (ASC) is rare and its origins are controversial. We here present a patient with oral ASC that developed after surgery for oral squamous cell carcinoma (SCC).Patient concerns:A 70-year-old man with SCC on the oral floor underwent surgical resection. However, the enlarged ulcer presented on the oral floor 9 month after surgery.Diagnoses:The biopsy of the ulcer revealed a SCC. Imaging examinations detected enhancement of a large lesion expanded to the tongue, but no evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…However, CK7 was negative, and CAM5.2 was positive only in a small number of cancer cells in the present case. The glandular components of reported cases of oral ASC were typically positive for CK7 [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The mucin-containing cells were CEA-positive and p40-negative, similar to the immunohistochemical results for ASC reported by Satomi et al [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CK7 was negative, and CAM5.2 was positive only in a small number of cancer cells in the present case. The glandular components of reported cases of oral ASC were typically positive for CK7 [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The mucin-containing cells were CEA-positive and p40-negative, similar to the immunohistochemical results for ASC reported by Satomi et al [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…From our comprehensive literature review of ASC arising in the oral cavity ( Table 1 ), 50 cases, including the present case, have been reported [ 2 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], and the clinical information of the review is summarized in Table 2 . The median age of the patients was 60 (range 22–97).…”
Section: Discussionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is the predominant subtype of oral cancer, 1 which is characterized by high incidence and mortality, and brought huge health burden to human beings worldwide. 2–4 Although the advances in the traditional therapies, such as surgery, chemotherapy and radiotherapy had been reached, the prognosis in OSCC patients is still very poor as the result of its unclear underlying mechanisms. 5–7 Therefore, researchers recently focused on exploring the molecular characteristics of OSCC pathogenesis, 4 , 8 and identified that multiple long non-coding RNAs (LncRNAs) participated in modulating OSCC development.…”
Section: Introductionmentioning
confidence: 99%